(3x-7)(2x+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

3x-7=0

2x+3=0

Set the first factor equal to 0.

3x-7=0

Add 7 to both sides of the equation.

3x=7

Divide each term by 3 and simplify.

Divide each term in 3x=7 by 3.

3×3=73

Cancel the common factor of 3.

Cancel the common factor.

3×3=73

Divide x by 1.

x=73

x=73

x=73

x=73

Set the next factor equal to 0.

2x+3=0

Subtract 3 from both sides of the equation.

2x=-3

Divide each term by 2 and simplify.

Divide each term in 2x=-3 by 2.

2×2=-32

Cancel the common factor of 2.

Cancel the common factor.

2×2=-32

Divide x by 1.

x=-32

x=-32

Move the negative in front of the fraction.

x=-32

x=-32

x=-32

The final solution is all the values that make (3x-7)(2x+3)=0 true.

x=73,-32

Solve Using the Square Root Property (3x-7)(2x+3)=0